2013
DOI: 10.1111/ppa.12169
|View full text |Cite
|
Sign up to set email alerts
|

Production of discernible disease phenotypes in Canna by five plant viruses belonging to the genera Potyvirus,Cucumovirus and Badnavirus

Abstract: Cannas are tropical and subtropical flowering perennial plants. The genus contains many species but most commercially grown cultivars are interspecific hybrids selected for their attractive foliage and flowers. Canna production is so lucrative that there are farmers and nurseries dedicated solely to its production. The specific issue that the canna industry faces is virus diseases. In this study, rhizomes of 24 canna cultivars were gathered and diagnostics conducted to detect Bean yellow mosaic virus (BYMV, Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…This isolate infected only 20% of the inoculated canna plants. The results of mechanical transmission attempts in this study were essentially similar to those reported by Rajakaruna et al (2014), which state that CaYSV is poorly transmitted by mechanical inoculation using sap from canna leaves.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…This isolate infected only 20% of the inoculated canna plants. The results of mechanical transmission attempts in this study were essentially similar to those reported by Rajakaruna et al (2014), which state that CaYSV is poorly transmitted by mechanical inoculation using sap from canna leaves.…”
supporting
confidence: 80%
“…Another potyvirus, Canna yellow streak virus (CaYSV), was reported in the United Kingdom in 2007, and other countries (Monger et al 2007;Rajakaruna et al 2014;Chauhan et al 2015). Although the canna lily is commonly found in nature as well as in public and private gardens in Brazil, to date there has been no reported occurrence of viral diseases in these plants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another badnavirus, Canna yellow mottle associated virus 1, was also found on canna (WIJAYASEKARA et al, 2017). CMV (LOKHARDT, 1988) and TAV (HOLLINGS and STONE, 1971) are less common in this crop (RAJAKARUNA et al, 2014). Viruses infecting canna were found in the UK, Belgium, the Netherlands, France, Italy, Austria, Israel, Kenia, India, Japan, Thailand, Brazil, the USA and Russia.…”
Section: Cannamentioning
confidence: 97%
“…Symptoms may significantly vary depending on the cultivar and may be masked in varieties with dark-colored leaves. Mixed infections with two or three viruses of different taxonomic groups are common in canna (RAJAKARUNA et al, 2014;CHAUHAN et al 2015;KUMARI et al, 2016;ZAKUBANSKIY et al, 2017).…”
Section: Cannamentioning
confidence: 99%